Recent increases in tropical cyclone intensification rates - Kieran T. Bhatia (Nature Portfolio, 2019)
Tropical cyclones that rapidly intensify are associated with the highest forecast errors and the strongest storms. This study shows that the proportion of tropical cyclones that rapidly intensify recently increased in the Atlantic basin, and that this trend is likely due to anthropogenic forcing.